2020
DOI: 10.1038/s41467-020-18527-0
|View full text |Cite
|
Sign up to set email alerts
|

A predictable conserved DNA base composition signature defines human core DNA replication origins

Abstract: DNA replication initiates from multiple genomic locations called replication origins. In metazoa, DNA sequence elements involved in origin specification remain elusive. Here, we examine pluripotent, primary, differentiating, and immortalized human cells, and demonstrate that a class of origins, termed core origins, is shared by different cell types and host ~80% of all DNA replication initiation events in any cell population. We detect a shared G-rich DNA sequence signature that coincides with most core origin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
83
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(116 citation statements)
references
References 68 publications
(142 reference statements)
9
83
1
Order By: Relevance
“…Other properties of TRF2 could also be involved in its role in pericentromeric replication initiation since it was reported that it associates to ORCA/LRWD1 [ 24 ] and that, in addition to the basic N-terminal domain, the TRF2 dimerization domain is required for ORC recruitment [ 25 ]. An interesting possibility would be that the pericentromeric ORI activity also relies on the ability of TRF2 to bind and unwind the formation of a G-quadruplex structure within the G-rich satellite DNA repeats [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other properties of TRF2 could also be involved in its role in pericentromeric replication initiation since it was reported that it associates to ORCA/LRWD1 [ 24 ] and that, in addition to the basic N-terminal domain, the TRF2 dimerization domain is required for ORC recruitment [ 25 ]. An interesting possibility would be that the pericentromeric ORI activity also relies on the ability of TRF2 to bind and unwind the formation of a G-quadruplex structure within the G-rich satellite DNA repeats [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…A limitation of this study is not to have analyzed the role of TRF2 in replication initiation in normal cells, particularly because it was reported that immortalization alters the ORI distribution within heterochromatin [ 26 ]. Nevertheless, besides having revealed a specific role of TRF2 in ORI activity within pericentromeres, this study paves the way towards a better understanding of the specific determinants of replication initiation within the highly repeated heterochromatin regions, a process which is still poorly investigated.…”
Section: Discussionmentioning
confidence: 99%
“…A cascade or domino model suggests that replication first initiates at the most efficient (master) origins, and then spreads to less efficient origins within an RTD (Boos & Ferreira, 2019;Guilbaud et al, 2011). Various processes and factors contribute to origin specification such as transcription, DNA sequences, histone variants, histone modifications, and nucleosome dynamics (Akerman et al, 2020;Cayrou et al, 2015;Long et al, 2019;Petryk et al, 2016;Prioleau & MacAlpine, 2016;O. K. Smith & Aladjem, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Origins of replication are of fundamental importance to ensure that DNA is copied only once during each cell cycle [ 36 ]. In humans, origins of replication seem to contain a G-rich DNA sequence signature that can be recognized by the origin recognition complex (ORC) [ 37 ]. The ORC complex directs the assembly of other factors, such as Cdc6, Cdt1 and the MCM2-7 complex, to form a prereplication complex (pre-RC).…”
Section: Mtorc1 Activity and Dna Synthesismentioning
confidence: 99%